Optimizing patients' functional status during daily nursing care interventions: A systematic review. Issue 5 (23rd August 2020) - Verstraten, Carolien C. J. M. M.; Metzelthin, Silke F.; Schoonhoven, Lisette; Schuurmans, Marieke J.; de Man‐van Ginkel, Janneke M.
Abstract: Patients often experience a functional decline due to physical inactivity during illness. Nurses can influence the physical activity of patients while assisting them with activities of daily living. The purpose of this study was to identify effective interventions that are embedded in daily nursing care (irrespective of care setting) that aim to optimize the functional status of patients by increasing their physical activity. A systematic review was performed and reported following the preferred reporting items for systematic reviews and meta‐analyses. PubMed, CINAHL, and Cochrane were searched for studies from January 2002 to March 2019. The critical appraisal tools from the Joanna Briggs Institute were used to assess the risk of bias in individual studies. Study characteristics, intervention key components, and reported effects of included studies were extracted, summarized narratively, and compared. Twenty studies, evaluating nine different interventions were included. In these interventions, eight key components were identified. Four components were included in all six interventions with a positive effect on mobility, physical activity, or functional status. These components were: assessment of patient's functionality; goal setting with the patient; establishment of an individualized plan; and engagement of patients in physical and daily activity. The effects were limited due to the risk of bias in the studies, small sample sizes, limited clinical meaning of the effects, and variability of the adherence to the interventions. Multicomponent interventions were the most promising to enhance the functional status of patients. Future research should evaluate these interventions using research methods aiming at producing more rigorous evidence.